Analysis of a novel reduced complexity diversity combining scheme - Lanante, Leonardo A. (2007)
Diversity schemes are known to increase the capacity of wireless systems using multiple antennas in the receiver. While high end applications can do this optimally using Maximal Ration Combining (MRC), commercial applications settles for suboptimal schemes like Selection Diversity (SD). SD however provides diminishing gains as the number of antenna branches increases. Optimum combining at present is mostly done digitally using estimates of the channel. This requires a suitably powerful Digital Signal Processor (DSP) especially for today's fast bit rate applications. The thesis proposes a new algorithm that uses real valued weights to reduce the complexity of coherent combining. The approach starts with Selection Diversity then combines the other signal branches using a simple scaling operation. The result is an algorithm that makes RF combining possible simply by scaling the signal branches. Simulation results reveal that Bit Error Rate (BER) performance of the proposed algorithm is just 0.7 dB and 1.6 dB below MRC for 2 and 4 antennas respectively in Rayleigh fading channels. The relative performance of the proposed algorithm becomes better in presence of channel estimation errors. When the channel is estimated using finite number of symbols, the proposed algorithm becomes increasingly better than EGC for 2 antennas.